2021
DOI: 10.3389/fnmol.2021.752838
|View full text |Cite
|
Sign up to set email alerts
|

A Noradrenergic Lesion Attenuates Surgery-Induced Cognitive Impairment in Rats by Suppressing Neuroinflammation

Abstract: Postoperative cognitive dysfunction (POCD) is a common postoperative neurocognitive complication in elderly patients. However, the specific pathogenesis is unknown, and it has been demonstrated that neuroinflammation plays a key role in POCD. Recently, increasing evidence has proven that the locus coeruleus noradrenergic (LCNE) system participates in regulating neuroinflammation in some neurodegenerative disorders. We hypothesize that LCNE plays an important role in the neuroinflammation of POCD. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…These findings were consistent with those reported by Wang et al, who showed that DSP-4 suppressed neuroinflammation caused by intestinal ischemia and attenuated cognitive impairment [ 49 ]. When dexmedetomidine was administered after DSP-4 administration, we found that DSP-4 could not attenuate the protective effect of dexmedetomidine on hippocampal inflammatory injury, and dexmedetomidine did not further enhance or weaken the effects of DSP-4.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were consistent with those reported by Wang et al, who showed that DSP-4 suppressed neuroinflammation caused by intestinal ischemia and attenuated cognitive impairment [ 49 ]. When dexmedetomidine was administered after DSP-4 administration, we found that DSP-4 could not attenuate the protective effect of dexmedetomidine on hippocampal inflammatory injury, and dexmedetomidine did not further enhance or weaken the effects of DSP-4.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating research findings show that the LCNE system is involved in neuroinflammation. Nonetheless, the role of LCNE in regulation of inflammation remains controversial[ 23 , 48 , 49 ]. To evaluate whether dexmedetomidine improved neuroinflammation and cognitive function through the LCNE system after intestinal ischemia/reperfusion injury in mice, we used the neurotoxic drug DSP-4 to selectively degrade LC norepinephrine neurons at 2 weeks and 1 week before operation, which was confirmed by immunofluorescence staining showing a significant decrease in TH-positive neurons in the LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has recently been shown that intracerebroventricular administration of DSP4 increases microglial and astrocyte activation, reducing the learning abilities of the animals as well as their memory. However, DSP4 treatment resulted in protective effects against hippocampal dependent learning and memory impairment due to surgery in a model of post operative cognitive dysfunction [ 76 ]. For this reason, the development of alternative ways to simulate the depletion of LC neurons could yield more reliable results.…”
Section: Reduction Of Lc and Na Activity: Evidence From Preclinical M...mentioning
confidence: 99%
“…For instance, in neurotoxin-based models of PD, reduction of brain NE is shown to increase neuroin ammation and dopaminergic neuron degeneration in the SNpc [4][5][6], while other studies nd no effect on dopamine levels or dopaminergic neuron survival after brain NE depletion [7][8][9][10]. Outside of PD pathologies, depletion of brain NE has been reported to be neuroprotective by reducing microglia activation [11]. These diverse responses re ect the many and complex physiological functions regulated by NE in the brain [12,13].…”
Section: Introductionmentioning
confidence: 99%